A Facile Review on the Legal Issues concerning the Implementation of the Administration of Criminal Justice Act of Nigeria - Aidonojie, Paul Atagamen (Sultan Agung Notary Law Review, 2024)
No doubt that the Administration of Criminal Justice Act of Nigeria 2015 brought innovative provisions in ensuring justice is served to the society. However, despite the innovative provision of the Act, there seem to be a high level of maladministration of justice. Given this, the study undertook doctrinal and non-doctrinal research on how effective the police, the prison officers, the office of the Attorney-General of Nigeria, and the court have been able to enforce their functions as provided by the ACJA of Nigeria. The study used online survey questionnaires sent to 302 legal practitioners (randomly selected) in Nigeria, given their pragmatic knowledge of ACJA of Nigeria. A descriptive and analytical statistic was used to analyse the respondents’ response in ascertaining if the above ministers of justice have been effective in enforcing their roles as specified by ACJA of Nigeria. Given the data generated, the study found that there has been a lapse in the effective implementation of ACJA in Nigeria. It was therefore concluded and recommended that the Administration of Criminal Justice Monitoring Committee set up by the ACJA of Nigeria need to exact their duties in check-mating the police, the office of AG of Nigeria, and the courts to ensure the maximum enforcement of their functions.